Improving Learning Outcomes on the Musculoskeletal System through Direct Instruction with Biology Magazines - Nabila, Nuruliza; Titin, Titin; Wahyuni, Eko Sri (Jurnal Pijar Mipa, 2025)
The students of class XI IPA 2 at MAN 1 Kubu Raya demonstrated low understanding of the musculoskeletal system, which resulted in poor learning outcomes. This issue stemmed from the dominance of a teacher-centered approach, where learning relied heavily on lectures guided by textbooks. A potential solution is the implementation of a structured learning model, such as direct instruction, which has the capacity to enhance student learning outcomes. Furthermore, integrating the direct instruction model with biology magazines can stimulate students’ interest, attention, and comprehension of the topic. This research aimed to examine the improvement of student learning outcomes on the musculoskeletal system through the application of the direct instruction model assisted by biology magazines in class XI IPA 2 at MAN 1 Kubu Raya. The research employed Classroom Action Research, conducted in two cycles, each consisting of two meetings following the stages of planning, implementation, observation, and reflection. The research subjects were 33 students of XI IPA 2, with instruments comprising observation sheets and learning outcome test sheets, both validated and confirmed reliable. Data analysis involved calculating the percentage of implementation based on observation results, followed by determining the percentage of classical achievement of learning outcomes. The findings revealed an increase in learning outcomes, from 78.18% in Cycle I to 84.40% in Cycle II, with learning implementation reaching 100% in both cycles. These results indicate that the use of the direct instruction model assisted by biology magazines can significantly improve student learning outcomes on the musculoskeletal system. This implies that integrating the direct instruction model with an innovative learning media (such as magazines) can provide structured, engaging, and comprehensive biology learning experiences that effectively enhance students’ learning outcomes.